Understanding Social and Environmental Accounting: Social and environmental accounting - Zulkifli, Norhayah (Asian Journal of Accounting Perspectives, 2008)
Literature on social and environmental aspects of accounting can be found since the early 1970s and the increase in the amount of research and interest is paramount. Consequently and at the same time the idea of accounting as a transcend element portrayed by social and environmental accounting (SEA) is being adopted by many quarters in companies’ accounting and reporting practices as well as management practices. Despite the substantial increase in SEA and reporting as well as management practices in many parts of the world, news on business’ implications with social and environmental problems tend to persist. The effectiveness of such practices could be due to adopting SEA and reporting without proper understanding of the whole concepts underlying the discipline. In this regard, a solid understanding of SEA as a new form of accounting is crucial so that those who practice actually embrace the concepts of SEA. This article reviews and analyses the different concepts of SEA with the intention to clarify the various and sometimes vague definitions of SEA.